SISTEM INFORMASI PADA PENYEWAAN ALAT CAMPING BERBASIS WEBSITE - Ridwan Ramadhan (2023)
In today's modern era, mountain climbing activities are becoming a trend, especially among young people. Because of this, many shops have opened camping equipment rental businesses, one of which is the CampsRent store. However, the camping equipment rental information system at RentCamps is currently still inefficient because it still uses conventional methods. In the process of ordering goods and managing goods, they still have to use books and the financial reporting process still uses a ledger. Based on this, the author provides the right solution to the problem that occurs by creating a website-based camping equipment rental information system that is connected to the internet so that it can make it easier for CampsRent and customers in the rental process and can also provide information regarding the status of returned goods for the shop. Camping equipment rental information system will be built using waterfall and PIECES analysis method. The PIECES analysis method is used to identify problems in the CampsRent store from several aspects including analysis of performance, information, economy, efficiency and service. In making this website using the programming language PHP, JS, and MYSQL database as data storage and as a testing phase using the black box testing method. In conclusion, through this website, customers can easily access product information and product prices, then the shop can also manage products, manage order data, and manage computerized financial reports.